Association between the CYP1A1 gene polymorphism and susceptibility to emphysema and lung cancer. Issue 4 (August 1995) - Cantlay, A M; Lamb, D; Gillooly, M; Norrman, J; Morrison, D; Smith, C A D; Harrison, D J
Abstract : Aim —To investigate cytochrome P4501A1 (CYP1A1) polymorphism and susceptibility to emphysema and lung cancer. Methods —A novel polymerase chain reaction (PCR) for genotyping the CYP1A1 polymorphism, corresponding to putative low or high enzyme activity, was developed to genotype lung cancer resection samples which had been assessed macroscopically for the presence of centriacinar and panacinar emphysema. Samples were collected and genotyped from a group of patients with chronic obstructive airways disease. A control group of anonymous blood donations was genotyped to determine the basal levels of the polymorphism in the Scottish population. Results —The high activity allele of the CYP1A1 gene is associated with susceptibility to centriacinar emphysema and lung cancer but not panacinar emphysema. CYP1A1 polymorphism is not linked to lung cancer in the absence of emphysema, nor to chronic obstructive airways disease which is the clinical manifestation of emphysema, particularly of the panacinar type. Conclusions —Susceptibility to emphysema and lung cancer is associated with polymorphism of the P4501A1 gene. A trend towards damage of centriacinar pattern has been detected, which supports the theory that centriacinar emphysema results from local, direct damage to the respiratory bronchioles from exposure to cigarette smoke.